Pelaksanaan Program PDS (Penerjunan Dosen ke Sekolah) sebagai Upaya Kolaborasi LPTK dengan Sekolah Mitra, Penguatan Kompetensi Profesionalisme Dosen Prodi PGSD UPY dan Pemecahan Permasalahan Sekolah Mitra SD Muhammadiyah Wirobrajan 2 Yogyakarta - Muhtarom, Taufik; Nofitasari, Anggun (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2023)
The purpose of this activity is to 1) approach self-approach between lecturers and partner schools to be able to carry out collaborative activities, 2) equip the lecturers with problem-solving skills in the field, 3) training lecturers to design a lesson that is expected to help solve partner school problems, 4) help solve problems faced by partner schools. The method of carrying out this activity is the discussion method, collaboration between lecturers and school principals and partner teachers and carried out through direct teaching practice in grade third of Muhammadiyah Wirobrajan 3 Elementary School by the PDS implementing lecturer, namely Taufik Muhtarom, M.Pd from Yogyakarta PGRI University. This program is carried out for 3 weeks starting from 10-30 November 2022. The result of this activity is that the implementation of lecturers' deployment to schools is able to improve the collaboration skills of lecturers and partner teachers for solving problems in class directly. The learning model offered by the implementing lecturer as a solution to problem solving in partner classes, namely the CTL learning model and the role playing learning model is able to increase student participation and involvement in learning, increase understanding of learning material and make students more motivated in participating in the learning process in class.